Assessing Fiscal Sustainability in Indonesia: Error Correction Mechanism Diagnostic - Gabriella Deby Laura; Rahmania Nur Chasanah; Nafisatul Faridah; Fitri Kartiasih (Jurnal Ekonomi Pembangunan, 2023)
Indonesia's debt is increasing and is not controlled properly, which will result in a fiscal budget deficit. This study aims to determine the condition of fiscal sustainability in Indonesia by looking at the factors that affect the debt-to-GDP ratio in 2012 Quarter I to 2022 Quarter II. Fiscal sustainability can be seen from the debt-to-GDP ratio proxy variable and the independent variables used are the previous quarter's debt ratio, economic growth, inflation, and the exchange rate. This research is a qualitative type with a brief descriptive about the state of the debt ratio and the variables that influence it and quantitatively using the Error Correction Mechanism (ECM) using statistical software called EViews. The results show that in the long term the debt-to-GDP ratio in Indonesia is significantly influenced by the previous quarter's debt ratio, economic growth, inflation, and the exchange rate. Meanwhile, in the short term, changes in the debt to GDP ratio are significantly influenced by changes in the debt ratio in the previous quarter, changes in economic growth, and changes in inflation.